2019
DOI: 10.5114/hpr.2019.87865
|View full text |Cite
|
Sign up to set email alerts
|

Mediatory effect of depression in the relations between cognitive reserve and cognitive abilities. Does a CR index matter?

Abstract: health psychology report • volume 7(3), 9 original article background Cognitive reserve (CR) explains the level of cognitive functioning in healthy aging individuals or those with brain dysfunctions. Various CR indexes include objective (e.g. education level), subjective (e.g. self-report methods of life activity), and their combinations. Data showing the impact of CR on cognitive performance are unclear due to the relationship between CR and depressive mood as well as due to the impact of depressed mood on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Research findings also showed associations between CR and gender, depression intensity and age. These results suggest that the individual variables mediate or moderate the relation between CRcognitive functions (Szepietowska, 2019).…”
Section: Cognitive Reserve: Critical Evaluation Of the Methodologymentioning
confidence: 76%
See 3 more Smart Citations
“…Research findings also showed associations between CR and gender, depression intensity and age. These results suggest that the individual variables mediate or moderate the relation between CRcognitive functions (Szepietowska, 2019).…”
Section: Cognitive Reserve: Critical Evaluation Of the Methodologymentioning
confidence: 76%
“…quantitative, objective data (e.g., years of education) and/or qualitative data (e.g., type of responsibility at work). Assessment of certain data comprised in CR is performed by study participants in a retrospective and subjective manner (Grotz et al, 2017;Szepietowska, 2019), as a result of which the accumulated data may be inaccurate; additionally, the relevant questionnaires do not account for early stages of development and specificity of socio-political circumstances. As an example, the Working Activity subscale in the CRIq (Nucci et al, 2012) distinguishes a few levels of intellectual involvement in work (including e.g.…”
Section: Cognitive Reserve: Critical Evaluation Of the Methodologymentioning
confidence: 99%
See 2 more Smart Citations